Terminal Cambrian and Early Ordovician (Tremadocian) conodonts from Eastern Alborz, north-central Iran. Issue 2 (2nd April 2016) - Jahangir, Hadi; Ghobadi Pour, Mansoureh; Ashuri, Alireza; Amini, Arash
Abstract : Hadi Jahangir, Mansoureh Ghobadi Pour, Alireza Ashuri & Arash Amini, December2015. Terminal Cambrian and Early Ordovician (Tremadocian) conodonts from Eastern Alborz, north-central Iran. Alcheringa ##, ###-###. ISSN 0311-5518. Uppermost Cambrian (Furongian) and Lower Ordovician (Tremadocian) deposits of eastern Alborz in northern Iran contain several successive low- to moderate-diversity conodont associations including 13 genera and 19 species of euconodonts, paraconodonts and protoconodonts, which define six biozones: 1, the Proconodontus muelleri ; 2, Eoconodontus notchpeakensis ; 3, Cordylodus andresi ; 4, Cordylodus proavus ; 5, Paltodus deltifer ; and 6, Paroistodus proteus zones. With the exception of Cordylodus andresi, which is otherwise known from Baltoscandia and from the Oaxaquia terrane (Mexico), all index-taxa are geographically widespread, allowing long-range correlation within the Cold Domain or the North Atlantic Province, and in particular with Baltica. Invasion of euconodonts in the Alborz region, defined by the first occurrence of Proconodontus muelleri, coincides closely with a steady rise in sea level and termination of carbonate sedimentation, whereas the transition from the Proconodontus muelleri to Eoconodontus notchpeakensis zones occurs during a highstand interval unlike in Laurentian sequences. The interval corresponding to the Cordylodus andresi and Cordylodus proavus zones, and the transition from the Paltodus deltifer to Paroistodus proteus zones coincided with unstable sea levels and the formation of shoal complexes. The lower boundary of the Floian Stage can be provisionally placed slightly below the first documented occurrence of Acodus sp. cf. A. kechikaensis, somewhat below the second unit of andesitic lava flows in the Simeh-Kuh section. Hadi Jahangir [ jahangir.hadi@gmail.com ] and Alireza Ashuri [ ashouri2001@yahoo.com ] Department of Geology, Faculty of Sciences, Ferdowsi University, Azadi Square, Mashhad 91775-1436, Iran; Mansoureh Ghobadi Pour* [ mghobadipour@yahoo.co.uk ;m.ghobadipour@gu.ac.ir ] and Arash Amini [ a.amini@gu.ac.ir ], Department of Geology, Faculty of Sciences, Golestan University, Gorgan 49138-15739, Iran. *Also affiliated with Department of Geology, National Museum of Wales, Cathays Park, Cardiff CF10 3NP, UK.